2011
DOI: 10.1177/1062860611399116
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Public Reporting of Central Line–Associated Bloodstream Infections by State

Abstract: Central line-associated bloodstream infections (CLABSIs) are common, costly, and largely preventable. Consumers who want high-quality care should have access to CLABSI rates to make health care decisions. The authors searched state health department Web sites for publicly available CLABSI data. Fourteen states, all with mandatory CLABSI monitoring laws, had publicly available data. The authors identified significant variation in the presentation of infection rates, methods of risk adjustment, locations and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…To account for possible non-independence of observations among NICUs from the same state, possibly due to factors such as statewide CLABSI reduction collaboratives 13, 14 or state law mandated CLABSI reporting, 15 we accounted for clustering by state, and Huber White robust standard errors were calculated. Possible heterogeneity in duration and BW-specific use of CL's across compliance categories, that could explain any observed association between overall CLABSI rates and the level of compliance in the primary model were also examined.…”
Section: Methodsmentioning
confidence: 99%
“…To account for possible non-independence of observations among NICUs from the same state, possibly due to factors such as statewide CLABSI reduction collaboratives 13, 14 or state law mandated CLABSI reporting, 15 we accounted for clustering by state, and Huber White robust standard errors were calculated. Possible heterogeneity in duration and BW-specific use of CL's across compliance categories, that could explain any observed association between overall CLABSI rates and the level of compliance in the primary model were also examined.…”
Section: Methodsmentioning
confidence: 99%
“…For example, CDC recently reported that CLABSI rates in US ICUs decreased 58% from 2001 to 2009. 1 These rates also are publicly reported in 14 states by mandate 22 and are used by CMS to qualify hospitals for their annual payment update. In addition, healthcareassociated-infections data are now available on the CMS Hospital Compare website (http://www.hospitalcompare.hhs .gov/), effectively reporting NHSN ICU CLABSI rates for all hospitals that receive reimbursements from Medicare.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our methodology cannot determine if these findings reflect more institutional attention to infection control practices in the setting of a state data submission mandate versus “gaming” the system. There is heterogeneity in the legal requirement for CLABSI data submission across states 7 that was not addressed, as we only considered the presence of mandatory data submission requirements and did not analyze other variations in provisions of HAI laws (e.g. public reporting, facility identifiers, use of risk adjustment).…”
Section: Discussionmentioning
confidence: 99%
“…The 2012 Centers for Disease Control and Prevention (CDC)/Association of State and Territorial Health Officials combined HAI prevention policy tool kit recommends public reporting of HAI data, 6 and many states have enacted statutes requiring mandatory CLABSI data submission. 7 The association of these mandates for HAI data submission with process and outcome measures for CLABSI prevention in pediatric settings has not been well described. We assessed whether the presence of state mandate for submission of neonatal intensive care units (NICU) CLABSI data was associated with CLABSI prevention policy compliance and/or CLABSI rates reported to CDC’s National Healthcare Safety Network [NHSN]) in a sample of NICUs in the U.S. We hypothesized that NICUs in states with legal mandates to submit CLABSI data would report greater compliance with CLABSI prevention practices and lower CLABSI rates than NICUs located in states without such mandates.…”
Section: Introductionmentioning
confidence: 99%